Pattern of sexually transmitted infections from a tertiary care hospital, Pokhara: A six-month retrospective study - Karki, Sushil; Adhikari, Sabina; Poudel, Pratima; Nepal, Anand (Asian Journal of Medical Sciences, 2023)
Background: Sexually transmitted infections (STIs) are major public health problem that have profound effect in reproductive and mental health. STIs have direct impact on sexual and reproductive health through stigmatization, infertility, and cancers and can increase the risk of HIV.2 Unprotected sexual contact with an infected partner is the most important risk factor associated with STI. Pattern of STI varies from region to region depending on socioeconomic status, ethnicity, and educational factor. Aims and Objectives: The aim of the study was to assess pattern of STIs in a tertiary level hospital, Pokhara. Materials and Methods: The following is a hospital-based retrospective study conducted in the Dermatology department of Pokhara academy of health sciences (PoAHS). All patients who attended the STI clinic of dermatology OPD from 2078/05/01 to 2078/11/30 B.S. with clinical manifestations of STI and associated positive serological investigation with their risky sexual behavior, related information was recorded in STI register and was analyzed. HIV cases are enrolled directly to antiretroviral therapy clinic of PoAHS, so HIV cases were not included in the study. Results: Out of 87 STI patients, 71.3% were males and 28.7% were females. The mean age of patient with STI was 31.34+8.4. The most common diagnosis was syphilis 55.2% followed by urethral discharge syndrome 16.1%. STIs were common among married individuals 74.7%. Most common high-risk sexual behavior among patients with STI was multiple sexual partners 79.3%. Conclusion: The study showed that the prevalence of STIs is still high in the society. Lack of awareness, delinquent behavior, and an inconsistent use of condoms during sexual contact may be the major contributing factors.